Power Measurement and Data Logger with High-Resolution for Industrial DC-Grid Application - Apse-Apsitis, Peteris; Senfelds, Armands; Avotins, Ansis; Paugurs, Arturs; Prieditis, Marcis (Electrical, Control and Communication Engineering, 2015)
Power and energy measurement and monitoring is a key factor for many industries in terms of energy and cost efficiency evaluation. Due to trends of Smart Grid concept application in industrial environment, including decentralized DC-Grid implementation, for precise evaluation – faster and low-cost measurement equipment is needed. Manufacturing industry widely uses industrial robots that have dynamic load characteristics for which faster measurement equipment is needed.